Pulmonary drug delivery with aerogels: engineering of alginate and alginate–hyaluronic acid microspheres. (28th May 2021) - Athamneh, Tamara; Amin, Adil; Benke, Edit; Ambrus, Rita; Gurikov, Pavel; Smirnova, Irina; Leopold, Claudia S.
Abstract: In this study, the aerogel technology was used to prepare pulmonary drug carriers consisting of alginate and alginate–hyaluronic acid by an emulsion gelation technique and supercritical CO2 drying. During the preparation process, the emulsification rate and inner phase viscosity were varied to control the diameter of aerogel microspheres. Results showed that the aerogel microspheres were highly porous (porosity > 98%) with low densities in the range between 0.0087 and 0.0634 g/cm 3 as well as high surface areas between 354 and 759 m 2 /g. The obtained microspheres showed aerodynamic diameter below 5 µm making them suitable for pulmonary drug delivery. An in vitro drug release study with the model drug sodium naproxen was conducted and a non-Fickian drug release mechanism was observed, with no significant difference between the release profiles of alginate and alginate–hyaluronic acid microspheres. During the emulsion gelation step, the feasibility of using the capillary number to estimate the largest stable droplet size in the emulsions was also studied and it was found that using this number, the droplet size in the emulsions may well be predicted.